Reconstruction of Transport Regulatory On Marine Toll to Support Sea Connectivity Based On Pancasila Justice - Hartanto Hartanto (Universitas Islam Sultan Agung, 2019)
The idea of marine toll is an attempt to realize the first Nawacita that is strengthening Indonesian identity as a maritime country and the third of Nawacita, that is to develop Indonesia from the periphery to strengthen these areas and villages within the framework of a unitary state, in addition to the marine toll is also a confirmation that the country is actually present to all areas through ships that visited the region. Accelerating infrastructure development in particular the implementation of toll expressway connectivity of sea or ocean (sea connectivity) if it can be done well it will be able to unite the archipelago by sea, especially to unite Indonesian islands in one national connectivity. Based on the documents of the National Medium Term Development Plan (RPJMN) 2015-2019, in the framework of the development of national connectivity to achieve a balance of development, the government has set a target increase of 24 strategic ports to support marine toll program. The marine toll presence is expected to drive the wheels of the economy efficiently and equitably so that Pancasila justice can be realized.Keywords: Reconstruction; Marine Toll; Connectivity; Pancasila Justice.